(untitled) (Far Eastern Federal University: School of Engineering Bulletin, 2023)
The results of the analysis of maritime island passenger traffic for the main socially significant routes for the period from 2018 to 2022 are presented. The design type and characteristics of ships carrying cargo and passengers on the considered island lines are considered and analyzed. The generalized results of a comparative analysis of the intensity of passenger traffic for the following traffic directions are presented: Vladivostok–Popov Island, Vladivostok–Reineke Island, and Vladivostok–Peschany Peninsula. As a result of the processing of statistical data, the patterns of development of island passenger traffic for the main socially significant routes were revealed and the corresponding laws for the distribution of volumes of cargo and passenger traffic were obtained.